Fluiditas Maskulinitas dan Feminitas dalam Boyband K-Pop sebagai Produk Industri Budaya - Dita Anggrahinita Yusanta (Kafa`ah: Journal of Gender Studies, 2019)
Fluidity between masculine and femininity both can represented by a K-Pop Boyband. It can be identified from all of their shows. They can carry the feminine and masculine concepts at the same time. Men with manly and a sixpack body, also could showed his cute and feminine side. This concept is considered as the redemption of men from toxic-masculinity. The question, is it really true that a men really have been freed. This is the main focus of this study. The object that will be observed is about Boyband K-Pop and literature review about soft-masculinity. This research used qualitative method, with interpretive qualitative descriptive analysis. Data collection in this study aims to present a description of the fluidity of masculinity and feminineity in K-Pop boybands. Based on the results of the study, the soft-masculinity concept in the K-Pop boyband  has become a product of the cultural industry, this can be proven by the many K-Pop boy bands are used as an attraction in various beauty products.